The development of the English domino game in basic spoken English class - Diana Oktavia; Renda Lestari (Lighthouse Publishing, 2022)
The goal of this study was to develop the domino game as a learning tool for Basic Spoken English students. The ADDIE (Analysis, Design, Development, Implement, and Evaluate) model was used for this investigation. This study was conducted in the English Department, with 30 students serving as subjects. These pupils were enrolled in a class called Basic Spoken English. The data collection instrument for this study was a questionnaire, a validation sheet, and an observation sheet. The validation was completed by subject matter experts and media specialists for learning and teaching English to determine whether or not the English Domino game can be used as a teaching and learning medium. The trial was done in a large group setting, with 30 students from STKIP Muhammadiyah Muara Bungo's English Department participating. The results indicate that the Domino game is an effective medium for teaching and learning to speak. The score for content validation was adequate, as was the score for media validation. Furthermore, the evaluation conducted by the lecturer of Basic Spoken English revealed that the English domino game was an excellent teaching and learning medium. Additionally, the observation score was 87.5, which is considered to be extremely good. As a result of the observation, it can be concluded that the developed Domino game not only encouraged students to be highly motivated to learn but also assisted them in improving their speaking abilities.